2011
DOI: 10.1071/an10183
|View full text |Cite
|
Sign up to set email alerts
|

On-farm paddock-scale comparisons across southern Australia confirm that increasing the nutrition of Merino ewes improves their production and the lifetime performance of their progeny

Abstract: Abstract. Experiments conducted by Lifetimewool at plot-scale have shown that differences in the maternal liveweight during pregnancy and lactation (liveweight profiles) of individual Merino ewes influences their wool production and reproductive rate as well as the birthweight, survival, weaning weight and lifetime wool production of their lambs in a predictable manner. This study determined whether these impacts of nutrition of the ewe on ewe and progeny performance are measurable on commercial properties acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…After 2 years of involvement in the program, the 182 participants surveyed who managed almost a million breeding ewes, increased their whole-farm stocking rate by 14%, increased lamb marking percentages by 11-13%, depending on enterprise, and reduced ewe mortality by 43%. The changes in productivity from adopting bestpractice nutritional management of ewes were consistent with those expected from and Behrendt et al (2011). The changes in productivity were also similar regardless of the enterprise type, which was surprising given the greater emphasis on reproduction rates in cross-bred enterprises (Warn et al 2006;Young et al 2010).…”
Section: Discussionsupporting
confidence: 61%
“…After 2 years of involvement in the program, the 182 participants surveyed who managed almost a million breeding ewes, increased their whole-farm stocking rate by 14%, increased lamb marking percentages by 11-13%, depending on enterprise, and reduced ewe mortality by 43%. The changes in productivity from adopting bestpractice nutritional management of ewes were consistent with those expected from and Behrendt et al (2011). The changes in productivity were also similar regardless of the enterprise type, which was surprising given the greater emphasis on reproduction rates in cross-bred enterprises (Warn et al 2006;Young et al 2010).…”
Section: Discussionsupporting
confidence: 61%
“…The high repeatability and small errors about the coefficients across years and sites (Tables 6-9) confirms the goodness of fit and predictability of the relationships derived in this study. Further validation of these relationships is also provided by the finding that the equations derived from individual ewes and their progeny in the present study were similar to those derived for whole flocks from a series of paddock-scale experiments conducted on farms across southern Australia (Behrendt et al 2011). In some cases the effects of the maternal environment on progeny clean fleece weight and fibre diameter decreased between hogget shearing and shearing at 51 months of age at the Vic.…”
Section: Discussionmentioning
confidence: 65%
“…By contrast, Behrendt et al (2011) reported that the effects of ewe liveweight profile during pregnancy on progeny fibre diameter were more apparent at the adult shearing than the hogget shearing for 13 different flocks across southern Australia. Kelly et al (2006) also reported that the adverse impacts of poor ewe nutrition during pregnancy on the fibre diameter of wool produced by the progeny were permanent.…”
Section: Discussionmentioning
confidence: 84%
“…Ferguson et al (2011) and Behrendt et al (2011) describe the design of the plot-(2 sites · 3 years) and paddock-scale (15 sites) experiments, respectively. In brief, the plot-scale experiments involved up to 1500 Merino ewes at two sites in each of 3 years.…”
Section: Relationship Between Change In Liveweight and Change In Condmentioning
confidence: 99%